The medieval reception of the Shahnama as a mirror for princes - Askari, Nasrin. (Studies in Persian Cultural History, 2016)
Nasrin Askari explores the medieval reception of Firdausī's Shāhnāma , or Book of Kings (completed in 1010 CE) as a mirror for princes. Through her examination of a wide range of medieval sources, Askari demonstrates that Firdausī's oeuvre was primarily understood as a book of wisdom and advice for kings and courtly elites. In order to illustrate the ways in which the Shāhnāma functions as a mirror for princes, Askari analyses the account about Ardashīr, the founder of the Sasanian dynasty, as an ideal king in the Shāhnāma . Within this context, she explains why the idea of the union of kingship and religion, a major topic in almost all medieval Persian mirrors for princes, has often been attributed to Ardashīr.